A comparison of coronary heart disease event rates among urban Australian Aboriginal people and a matched non-Aboriginal population. Issue 4 (28th April 2010) - Bradshaw, Pamela J; Alfonso, Helman S; Finn, Judith; Owen, Julie; Thompson, Peter L
Abstract : Background: Age-specific death from cardiovascular disease among Australian Aboriginals is estimated to be four to seven times that of general population, and the major cause of premature death. There is little reliable information on the incidence of coronary heart disease (CHD). This study compares CHD event rates in urban-dwelling Aboriginal people and the general population. Methods: The Perth Aboriginal Atherosclerosis Risk Study (PAARS) cohort was assessed at baseline (1998/1999) and 913 participants followed-up to 2006. A comparison group of age-matched, sex-matched and postcode-matched non-Aboriginals (n=3582) were selected from the Perth, Western Australia, Electoral Roll. Electronic record linkage captured prior CHD and first CHD events in both groups. The rates of first CHD events (hospital admission or CHD death) per 1000 person years (PY) and incidence rate ratios (IRR) were calculated. Results: The event rate for the PAARS population was 14.9 per 1000 PY (95% CI 12.3 to 18.2) versus 2.4 (1.9 to 3.1) for the general population. The IRR was 6.1 (4.5 to 8.4). For Aboriginal men the rate was 15.0 (11.2 to 20.0) versus 3.8 (2.5 to 5.0) per 1000 PY, with age-specific rates being two to five times that of non-Aboriginals. Incidence for Aboriginal women was 15.0 (11.5 to 19.5) versus 1.4 (0.9 to 2.1) with age-specific rates being 8–25 times that of non-Aboriginals. Conclusions: Age and sex-specific CHD event rates in urban Aboriginals far exceeded that of a matched general population. Events occurred at a much younger age among the Aboriginal participants and were equally excessive among men and women.